Nexus Between Crude Oil and Stock Market Return: Case of India - Mitra, Pradip Kumar (Asian Journal of Empirical Research, 2018)
Crude oil is an important driver of Indian economy and therefore, it is important to investigate whether the movement in crude oil prices affects the return of stock market indices. This paper examines the impact of return from crude oil on the return of some major Indian stock market indices. The construct was made from daily data from 2005 to 2016 to calculate the daily return of crude oil and four different stock market indices. Two different tests were carried out, namely, Granger causality test and Johansen cointegration test. Granger causality test was conducted to know the relationship between the return from crude oil and stock market indices, whereas, Johansen cointegration test was carried out to understand whether the long run equilibrium relationship is there between the dataset of returns? The result from the Granger causality test suggests that there is causality between the crude return and the return from stock market indices. The nature of causality is unidirectional in nature where crude return affects the return of the stock market indices. The results from Johansen cointegration test suggest that there exists a long run equilibrium relationship among these variables.